Early Outcome of Mitral Valve Replacement in Patient Having Mitral Stenosis with Moderate Pulmonary Hypertension - Zaman, MH; Rahim, AM Asif; Rashid, MZ; Hasan, MK; Islam, MS; Sharker, MK (Cardiovascular Journal, 2021)
Background: Mitral valve replacement (MVR) plays a central role in the management of patients with mitral stenosis with moderate to severe pulmonary hypertension. Pulmonary hypertension has an impact on short term outcome of MVR. It can influence left ventricular function (low output syndrome), incidence of arrhythmia, ARDS leading to respiratory failure and right ventricular failure which may be irreversible. Methods: The immediate postoperative hemodynamics in 40 patients with moderate to severe pulmonary arterial hypertension who underwent mitral valve replacement (BLMV) between July 2010 and June 2012 were studied prospectively. Patients were divided into two groups: Group A (n=20): Patient having MS with moderate pulmonary hypertension (PASP: 40-59 mm-Hg) and Group B (n=20): Patient having MS with severe pulmonary hypertension (PASP e” 60mm-Hg). Total two follow up were done- 1st follow up after 10 days and 2nd follow up after 1 month of MVR. Each patient was assessed by medical history, clinical examination & color doppler echocardiogram. Results: It was shown that surgery can be beneficial for the patients if MVR is done in the state of mild PAH irrespective of age but beyond this level of PAH, the patients may still remain with mild pulmonary hypertension which may trigger the cascade of pulmonary vascular Disease may be the cause of unsatisfactory outcome. So, early surgical outcome of mitral stenosis with moderate pulmonary hypertension is better than mitral stenosis with severe pulmonary hypertension. Conclusion: We conclude that MVR in patients having MS with moderate PAH is a safe and effective measures for preventing pulmonary hypertension related complications. Cardiovasc. j. 2021; 13(2): 177-182